200 Years in Innovation of Continuous Distillation1. Issue 1 (12th February 2014) - Kockmann, Norbert
Abstract Distillation is one of the oldest and most frequently used purification methods today. In 1813, Jean‐Baptiste Cellier‐Blumenthal patented the first continuously working distillation column, starting an impressive development of process equipment. New product areas were discovered as well as improved equipment installations. 100 years ago, Fritz Raschig patented his rings as packing material. Current developments are guided by deeper knowledge of heat and mass transfer as well as the integration of various process functions.